2011
DOI: 10.1002/pd.2803
|View full text |Cite
|
Sign up to set email alerts
|

Laser therapy for twin‐to‐twin transfusion syndrome (TTTS)

Abstract: Monochorionic twins are subjected to specific complications which originate in either imbalance or abnormality of the single placenta serving two twins including twin-to-twin transfusion syndrome. The diagnosis is well established in overt clinical forms with the association of polyuric polyhydramnios and oliguric oligohydramnios. The best treatment of cases presenting before 26 weeks of gestion is fetoscopic laser ablation of the intertwin anastomoses on the chorionic plate. Although subjected to subtle varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 98 publications
1
74
0
6
Order By: Relevance
“…In comparison, the rate of residual patent placental vascular anastomoses after SLPCV by our group, using similar technique and technology, has consistently been less than 5%, with no anemia after demise of the co-twin, and an incidence of reverse or persistent TTTS of only 1-1.5% (USFetus Consortium; . In view of the relatively high incidence of residual patent placental vascular anastomoses seen by some groups, some authors proposed 'connecting the dots' between photocoagulated areas on the surface of the placenta (Chalouhi et al, 2011). The premise behind this idea was that by lasering areas between laser-ablated placental vascular anastomoses, such 'blind lasering' would capture 'anastomoses' that would otherwise be missed (i.e., 'not visible'; Lewi et al, 2006).…”
Section: Connecting the Dots: The 'Solomon' Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the rate of residual patent placental vascular anastomoses after SLPCV by our group, using similar technique and technology, has consistently been less than 5%, with no anemia after demise of the co-twin, and an incidence of reverse or persistent TTTS of only 1-1.5% (USFetus Consortium; . In view of the relatively high incidence of residual patent placental vascular anastomoses seen by some groups, some authors proposed 'connecting the dots' between photocoagulated areas on the surface of the placenta (Chalouhi et al, 2011). The premise behind this idea was that by lasering areas between laser-ablated placental vascular anastomoses, such 'blind lasering' would capture 'anastomoses' that would otherwise be missed (i.e., 'not visible'; Lewi et al, 2006).…”
Section: Connecting the Dots: The 'Solomon' Techniquementioning
confidence: 99%
“…Such authors believed that, in fact, not all of the placental vascular anastomoses can be identified endoscopically (Lewi et al, 2006), and that therefore, ablating only the visible ones using the selective technique could miss vascular anastomoses and explain their high rate of residual patent placental vascular anastomoses. The resulting surgical technique of 'connecting the dots' was dubbed 'the Solomon technique' (Chalouhi et al, 2011), in reference to the biblical passage where, in order to resolve a dispute between two alleging mothers of a child, King Solomon proposed to cut the baby in half (1 Kings 3:16-28, NIV). The analogy, therefore, is that by lasering the areas of the placenta between endoscopically identified and laser-ablated vascular anastomoses, the placenta would be 'cut in half' .…”
Section: Connecting the Dots: The 'Solomon' Techniquementioning
confidence: 99%
“…Considered a minimally invasive procedure, FLS necessitates the insertion of a trocar into the amniotic cavity of the recipient twin to allow for insertion of the fetoscope (through a cannula which stays in place throughout the procedure) (11). A laser is used to seal the abnormal blood vessel anastomoses between the monochorionic twin placentas.…”
mentioning
confidence: 99%
“…Membrane folding or intertwin disparity in fetal growth, nuchal translucency thickness or amniotic fluid volumes are early signs of the possible development of TTTS and indicate the need for increased ultrasound surveillance of monochorionic pregnancies. This syndrome can also be suspected by acute maternal symptoms related to polyhydramnios (uterine distension, uterine contractions, dyspnea) (Chalouhi et al, 2011). The diagnosis relies upon strict ultrasound criteria as defined in the Eurofetus trial (Senat et al, 2004) and consist of a polyuric polyhydramnios in the recipient twin with a deepest vertical pool of at least 8.0 cm at or before 20 weeks of gestation or 10.0 cm after 20 weeks of gestation together with a distended fetal bladder, with oliguric oligohydramnios in the donor twin, showing a deepest vertical pool of at most 2.0 cm.…”
Section: Twin-to-twin Transfusion Syndrome (Ttts)mentioning
confidence: 99%
“…It is a hemodynamic, and probably hormonal, discordance secondary to imbalanced blood flow through the vascular anastomoses (Hubinont et Fisk, 1990) (Chalouhi et al, 2011). The natural history of untreated TTTS leads to intra-or perinatal death in 90% of cases (Robyr et al, 2006).…”
Section: Twin-to-twin Transfusion Syndrome (Ttts)mentioning
confidence: 99%